2005
DOI: 10.1002/masy.200551016
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Films for Wound Dressing Applications

Abstract: Polyurethane films based on renewable sources were prepared as an alternative to petroleum‐based polyurethane. The effects of the structure and ratio of diisocyanate components on polymer properties were investigated. Hexamethylene diisocyanate (HMDI) and diphenylmethylene diisocyanate (MDI) were chosen as the diisocyanate components in polymer synthesis. Membranes were prepared by casting‐evaporation technique and characterized for their gas permeability, film and mechanical properties. The oil‐based membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…[1] Due to their versatility, polyurethanes have been successfully employed in a wide range of applications, for example, biomaterials, construction, adhesives, fibers and coating. [2][3][4][5][6][7][8] Castor oil (CO), represented in Figure 1, is a low-cost, abundantly available, renewable raw material and has attracting research effort because of its use in coatings, adhesives, paints, sealants, encapsulating compounds. As a vegetable oil with reactive hydroxyl functional groups, it can be used as a polyol to develop new and ''green'' macromolecular architectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Due to their versatility, polyurethanes have been successfully employed in a wide range of applications, for example, biomaterials, construction, adhesives, fibers and coating. [2][3][4][5][6][7][8] Castor oil (CO), represented in Figure 1, is a low-cost, abundantly available, renewable raw material and has attracting research effort because of its use in coatings, adhesives, paints, sealants, encapsulating compounds. As a vegetable oil with reactive hydroxyl functional groups, it can be used as a polyol to develop new and ''green'' macromolecular architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethanes based on CO with different diisocyanates seem to be interesting alternatives to non-renewable-based materials, in agreement with the concept of sustainable development. There are several reports related to the elaboration of polyurethanes, such as IPNs [9,10] cast elastomers [8,11] and polyurethane coatings. [12] Different characterizations and analysis have been carried out on these systems.…”
Section: Introductionmentioning
confidence: 99%
“…In literature it is emphasized that the chemistry of a polyurethane membrane has an important effect on biocompatibility [14]. In our previous study, triglyceride oil-modified polyurethane films for wound dressing applications were prepared from linseed oil-based hydroxyl containing material and hexamethylene diisocyanate (HMDI) and/or diphenylmethylene diisocyanate (MDI) [15]. It was found that the amount and type of diisocyanates affected the film and mechanical properties, and gas permeability of polymeric membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Since these oils contain conjugated trienoic acids, polymers prepared from them have good film properties such as a short drying time and good water, alkali and acid resistances. Oil-modified polyurethane films were prepared from HMDI and/or MDI for wound-dressing applications [121]. It was found that the amount and type of diisocyanates affected the mechanical properties and gas permeabilities of polymeric membranes.…”
Section: Synthesis Of Waterborne Sunflower Oil Modified Urethanementioning
confidence: 99%